Factors Affecting the Need for Feasibility Analysis (For Local Construction Projects) - Muneer Anees; Syed Mustafa Hussain; Kamran Khan; Agha Taqi Abbas (Sir Syed University Research Journal of Engineering and Technology)
In Pakistan, the majority of the local construction projects are opted without feasibility analysis on the basis of previously worked data without examining the current scenario. However, for foreign-funded project feasibility analysis along with standard guidelines is conducted, but in case of domestically funded projects, it is often omitted. This research has uncovered critical factors affecting feasibility for the local construction industry of Pakistan. Field data are extracted from ongoing construction projects which are domestically funded. Relative Importance Index (RII) analysis was carried out first to rank the factors in terms of their perceived importance. Spearman’s rank correlation analysis was also done in this regard. The findings of the study might promote construction practitioners to focus on the need for feasibility analysis for local projects too.